‘Just tourism’ or Justice tourism? : analysis of the experience and outcomes of the first Native Nations cultural exchange in 2023 - Scheyvens, Regina; Kaire-Gataulu, Terina (Institute of Development Studies, Massey University, 2024)
This report discusses the findings of independent research conducted to analyse the impacts of the first Indigenous youth exchange programme organised under the programme, Native Nations: Tracing Indigenous Footsteps. Of note, the name of this programme was devised by the first group of rangatahi (Māori youth) to take part in this exchange.
IDS Working Paper 2024/1